Developing a performance story report: user guide - Roughly, A.; Dart, J. (Commonwealth of Australia, 2009)
This report is a nuts and bolts guide to developing a Collaborative Ou tcomes Report (COR)/ Performance Story Report (PSR) produced by the Au stralian Government and Jess Dart. It includes practical tips, step-by -step process guides and definitions of key concepts surrounding these approaches.